Research on the relationship of consumers’ social capital, green trust and the continuous buying intention of green agricultural products - Guo, Le; Rohani, Endut Intan; Xu, Xiaopeng (Edelweiss Applied Science and Technology, 2025)
The advantages and characteristics of private domain traffic channels have not been fully demonstrated, nor have they solved the problem of insufficient consumer trust. The purpose of this study is to analyze the relationship between consumer social capital elements, green trust, and the continuous buying intention of green agricultural products. Building on previous research, this study constructs a conceptual framework of the influencing factors on the continuous buying intention of green agricultural products based on SOR theory and proposes research hypotheses. Quantitative research was selected as the methodology, utilizing a questionnaire to collect primary data. By constructing a structural equation model, the relationships among the variables were explored and validated. The findings indicate that social capital indirectly influences the repurchase behavior of green agricultural products through green trust, with relational social capital demonstrating significantly stronger effects. Future research should address limitations related to sampling and methodology, explore multi-dimensional social capital and contextual factors further, and provide empirical support for enterprises to develop trust-centric green marketing strategies.